Preparation and in vivo study of 124I-labelled monoclonal antibody H17E2 in a human tumour xenograft model. A prelude to positron emission tomography (PET). - Snook, D. E. (Nature Publishing Group, 1990)
Positron emission tomography (PET) is a powerful nuclear medicine technique which, unlike conventional gamma camera tomography, relies on the coincidental detection of the two 511 keV gamma photons produced from the annihilation of a single positron. Hence good spatial resolution and accurate quantitation may be achieved. 124I (t1/2 = 4 days), a positron-emitting isotope of iodine, was chosen for our initial PET studies because the techniques of antibody radio-iodination are well established. The murine monoclonal antibody H17E2 detecting placental alkaline phosphatase (PLAP) was radiolabelled using the Iodogen method. A specific activity of 2.3 microCi microgram-1 was achieved with a radiolabelling efficiency of 91%. Nude mice bearing subcutaneous HEp2 human tumour xenografts (a PLAP expressing cell-line) received 8.3 micrograms (18.8 microCi) of H17E2-124I by intraperitoneal injection. Animals were killed and dissected at 5 h, 1, 2, 3, and 7 days, and radioactivity was assessed in tumour and normal tissues. The half-life in the blood of H17E2-124I was 132 h as compared with 141 h for H17E2-131I. Activity in tumour rose to 4.26% injected dose g-1 by 48 h and remained at this level until day 7, giving a tumour:blood ratio of 0.78 at this time. The percentage injected dose g-1 in all tissues (with the exception of tumour) decreased with time giving tumour:tissue ratios greater than 1.00 from 24 h onwards in all cases except blood. In conclusion, tumour localization of H17E2-124I has been successfully achieved in this animal model. This demonstrates the feasibility of using tumour-associated monoclonal antibodies radiolabelled with a positron-emitting isotope for tumour localization studies.